Guidelines for Implementing Innovations in Hospital Organizations - Josiano Cesar de Sousa; Miriam Borchardt; Murilo Barros Alves; Edithe Oliveira Nogueira (BBR: Brazilian Business Review)
This article presents an approach on the theory of innovation in services and aims to propose a set of guidelines to support management during the implementation of innovations in hospital organizations. A case study was carried out with two hospitals in the northeastern region of Brazil to seek an answer to the following research question: What guidelines can be proposed to support management during the process of implementing innovations in hospital organizations? The collected data were treated with content analysis techniques with the aid of the Atlas.ti software. As a result, it was possible to structure a set of guidelines composed of five stages, capable of supporting the management team during the process of implementing innovations in hospital organizations. The proposed guidelines indicate that to implement innovations, the hospital must arouse to the need to innovate, learn to innovate, reconfigure the environment, implement innovations and monitor results. The article adds academic contributions by exploring the theory of innovation and associating it with the service sector. It presents managerial contributions by proposing a set of guidelines for the implementation of innovations in hospital organizations. Finally, the article presents its limitations and recommendations for future research.